Pelatihan Pembuatan Nugget Ikan Patin di Desa Gohong Kecamatan Kahayan Hilir, Kabupaten Pulang Pisau - Marcelino Fangebean; Tambunan, Ellen Christ; Manurung, Lidya Maret Invanka; Simamora, Giofanny (Jurnal Pengabdian Kampus, 2024)
Gohong Village is one of the villages in the Kahayan Hilir Sub-district, Pulang Pisau Regency, Central Kalimantan Province. The village has an area of ±51,037 Ha. The potential in Gohong Village is the abundance of fish with annual production reaching out around 6-8 tons. The type of fish cultivated among them is catfish. The nutritional content of catfish is fatty acids omega-3. Omega-3 fatty acids found in the head are 2.28%, in the belly flap meat (belly meat) of 2.11%, and in the stomach contents of 1.45%. Training and assistance in making nuggets made from catfish was carried out by the PPK Ormawa HIMATRIPA Team in 2024 by utilizing the potential in Gohong Village to improve the community's economy. The Student Organization Capacity Strengthening Program (PPK ORMAWA) in this case is the Association of Agroindustrial Technology Department (HIMATRIPA) is a program to strengthen the capacity of ormawa through a series of ormawa coaching processes by universities which are implemented in community service and empowerment programs. The methods used in this activity are an initial survey to determine the potential of Gohong Village, Focus Group Discussion also training (demonstration) and assistance in making nuggets, and evaluation through questionnaires. Based on the evaluation carried out before and after the activity, nuggets were produced, an entrepreneurial group was formed, there was an increase in the knowledge and skills of the target community.